2023
DOI: 10.1161/circheartfailure.122.009745
|View full text |Cite
|
Sign up to set email alerts
|

Racial Inequities in Access to Ventricular Assist Device and Transplant Persist After Consideration for Preferences for Care: A Report From the REVIVAL Study

Abstract: Background: Racial disparities in access to advanced therapies for heart failure (HF) patients are well documented, although the reasons remain uncertain. We sought to determine the association of race on utilization of ventricular assist device (VAD) and transplant among patients with access to care at VAD centers and if patient preferences impact the effect. Methods: We performed an observational cohort study of ambulatory chronic systolic HF patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 55 publications
2
25
1
Order By: Relevance
“…These findings reflect previously described differences in not only the incidence and outcomes for heart failure in the African American community, with this population experiencing the highest rate of HF related morbidity and mortality and delayed presentation, but also perhaps differential application of advanced therapies 3,23–25 . Although African Americans with HF tend to be less often referred for advanced therapies in general, when deciding between LVAD and transplant, there appears to be a tendency to offer Black patients LVAD 3,26 . While there may be racial differences in the pathophysiology of heart failure, the differences in outcomes cannot be attributed solely to biologic differences 27–29 Furthermore, we demonstrated that non‐white recipients were more likely to have public insurance and that public insurance was associated with inferior outcomes.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings reflect previously described differences in not only the incidence and outcomes for heart failure in the African American community, with this population experiencing the highest rate of HF related morbidity and mortality and delayed presentation, but also perhaps differential application of advanced therapies 3,23–25 . Although African Americans with HF tend to be less often referred for advanced therapies in general, when deciding between LVAD and transplant, there appears to be a tendency to offer Black patients LVAD 3,26 . While there may be racial differences in the pathophysiology of heart failure, the differences in outcomes cannot be attributed solely to biologic differences 27–29 Furthermore, we demonstrated that non‐white recipients were more likely to have public insurance and that public insurance was associated with inferior outcomes.…”
Section: Discussionsupporting
confidence: 78%
“…3,[23][24][25] Although African Americans with HF tend to be less often referred for advanced therapies in general, when deciding between LVAD and transplant, there appears to be a tendency to offer Black patients LVAD. 3,26 While there may be racial differences in the pathophysiology of heart failure, the differences in outcomes cannot be attributed solely to biologic differences [27][28][29] Furthermore, we demonstrated that non-white recipients were more is often an imprecise term, and that we have not included individuals who identified as having a mixed racial background.…”
Section: Discussionmentioning
confidence: 99%
“…Given the proven, substantial clinical benefit of this treatment, the persistence of disparities in revascularization remains a significant cause of concern 3 decades after these disparities were first described . It is unlikely that patient preferences alone can explain these disparities given that similar disparities have been observed in the allocation of heart transplants and ventricular assist devices after accounting for patient preferences . These inequities likely reflect a combination of structural racism, which can impact access to high-quality care based on systematic historical divestment in predominantly Black communities, and individual or interpersonal racism, which can influence a clinician’s likelihood of referring patients for appropriate procedures …”
Section: Discussionmentioning
confidence: 99%
“…A 2023 study using REVIVAL-IT data, which studied ambulatory HF patients receiving care at LVAD centers, found that black patients were significantly less likely to receive an LVAD or transplant than white patients, regardless of patient preferences for advanced therapies. 21 Although this finding does clarify the relationship between race and LVAD utilization by removing potential issues of access at non-LVAD centers, it does not control for issues with access to follow up and evaluation appointments. Moreover, it examines patients recruited in 2015–2016, before FDA approval of the Heartmate 3 LVAD and the 2018 changes in the UNOS allocation system, both of which impacted LVAD utilization for reasons separate from race.…”
Section: Discussionmentioning
confidence: 91%